An Exploration of Underrepresentation of Aboriginal Cancer Patients Attending a Regional Radiotherapy Service in Western Australia. - Lyford, M.; Haigh, M.; Baxi, S.; Cheetham, Shelley; Shahid, Shaouli; Thompson, S. (Molecular Diversity Preservation International (MDPI), 2018)
Travel logistics impede Aboriginal patients' uptake of cancer treatments and is one reason for the poorer outcomes of Aboriginal people with cancer. This research examined benefits of a newly established rurally based radiotherapy unit in southwest Western Australia (WA), and included exploring the experience of Aboriginal patients and possible reasons for Aboriginal people's underrepresentation in treatment. Semi-structured in-depth interviews with 21 service providers involved in the treatment and care of people with cancer, and 3 Aboriginal patients with cancer who undertook radiotherapy at the Service were undertaken. Data were subject to thematic analysis involving immersion in the data for familiarization, inductive coding, investigator discussion and refining of emerging themes and triangulation of patient and provider interviews. Aboriginal cancer patients were positive about the treatment and support they had received, highlighting the often complex challenges faced by rural Aboriginal cancer patients in accessing and maintaining treatment. Service providers offered suggestions for small numbers presenting to the Service, including late presentation, potential perceptions of cultural insensitivity on the part of service providers, out-of-pocket costs and under-ascertainment of Aboriginal status. The Service has put in place practices and initiatives to support patient health and wellbeing, including making the facility more welcoming towards Aboriginal people and ensuring culturally appropriate care.